The Dog Schema - Umberto Eco; Maurizio Ferraris; Diego Marconi (Rivista di Estetica, 2021)
The Dog Schema is the translation of the Italian text Lo schema del cane, originally published in Rivista di Estetica in 1998. The text presents the debate among the philosophers Umberto Eco, Maurizio Ferraris, and Diego Marconi concerning the dog schema. The debate develops through a reflection on Kantian schematism and conceptual applications, showing three different points of view on the subject.